Effect of Microbial (Jeevatu) Treatment on Rice (Oryza sativa L.) Production - Adhikari, Suraj Raj; Paudel, Khadga Bhakta; Pokhrel, Kusum; Paudel, Amrita (International Journal of Applied Sciences and Biotechnology, 2013)
JeevatuTM is a consortium of beneficial natural microbes, available in liquid form. The yield of rice was observed vigorously high in Jeevatu based rice cultivated plant. The seed production in per spikelet is 237.1±44.92 in Jeevatu based and 179.4±25.26 in chemical based rice plant. In case of vegetative growth, 173.1±6.34 cm and 140.9±11.11 cm in Jeevatu based rice plant and chemical based methods respectively. Similarly the length of stalk of spikelet is 27±1.63cm and 22.1±2.23 cm was observed in Jeevatu based and chemical based respectively. The number of stalk in lumps is 16.2±1.75 and 12.2±2.20 in Jeevatu and chemical based paddy plant respectively under the same environment and physical factors. DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9134 Int J Appl Sci Biotechnol, Vol. 1(4): 184-188